Validation of a chemiluminescent assay for specific SARS-CoV-2 antibody - Tré-Hardy, Marie; Wilmet, Alain; Beukinga, Ingrid; Dogné, Jean-Michel; Douxfils, Jonathan; Blairon, Laurent (Clinical chemistry and laboratory medicine, 2020)
Objectives Faced with the COVID-19 pandemic and its impact on the availability and quality of both therapeutic and diagnostic methods, the Belgian authorities have decided to launch a procedure for additional evaluation of the performance of serological tests offered for sale on the national territory. This has been proposed with a double aim: (1) an in-depth verification of the analytical and clinical performances presented by the manufacturer and (2) an economy of scale in terms of centralized validation for all the laboratories using the tests subject to evaluation. Methods A retrospective validation study was conducted including the serum of 125 patients in order to determine the analytical and clinical performances of the LIAISON®SARS-CoV-2 from DiaSorin® detecting anti-SARS-CoV-2 IgG and to compare its clinical performance with the enzyme-linked immunosorbent assay (ELISA) test from Euroimmun®, one of the first commercially available tests allowing the detection of anti-SARS-CoV-2 IgA and IgG. Results The performances of the LIAISON®SARS-CoV-2 satisfied all the acceptance criteria and provided "real world" analytical and clinical performances very close to the ones reported by the manufacturer in its insert kit. Comparison between the LIAISON®SARS-CoV-2 and the ELISA method did not reveal any difference between the two techniques in terms of sensitivities and specificities regarding the determination of the IgG. Conclusions This study reports the validation of the LIAISON®SARS-CoV-2 allowing to detect IgG antibodies specifically directed against SARS-CoV-2. The analytical and clinical performances are excellent, and the automation of the test offers important rates, ideal for absorbing an extension of testing.